1987
DOI: 10.1002/1097-0142(19870201)59:3<501::aid-cncr2820590325>3.0.co;2-h
|View full text |Cite
|
Sign up to set email alerts
|

Langerhans cells and prognosis in patients with gastric carcinoma

Abstract: Infiltration of Langerhans cells (LC) and macrophages into tumor tissues was investigated using immunohistochemical methods, anti-S-100 protein and anti-lysozyme antibodies in 174 cases of gastric carcinoma. Varying population densities of S-100-positive LC were noted in tumor tissues; lysozyme-positive macrophages, however, were found in almost equal quantities. LC were mainly interspersed among the tumor cells, whereas macrophages were present in the stroma and around the necrotic foci. Although the survival… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
52
2
1

Year Published

1991
1991
2006
2006

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 121 publications
(56 citation statements)
references
References 17 publications
(2 reference statements)
1
52
2
1
Order By: Relevance
“…The prognostic significance of tumour-associated inflammatory cells is less clear in gastro-oesophageal cancer. An increased macrophage infiltrate was associated with more advanced stage of disease among patients with gastric cancer in one study, whereas other studies have suggested a more favourable prognosis associated with a more pronounced macrophage infiltration (Heidl et al, 1987;Tsujitani et al, 1987;Ohno et al, 2003). Similarly, increasing tumour-infiltrating lymphocyte count has been linked with decreased risk of death from gastric cancer in one study, but associated with an adverse prognosis in another (Setala et al, 1996;Grogg et al, 2003).…”
Section: Discussionmentioning
confidence: 81%
“…The prognostic significance of tumour-associated inflammatory cells is less clear in gastro-oesophageal cancer. An increased macrophage infiltrate was associated with more advanced stage of disease among patients with gastric cancer in one study, whereas other studies have suggested a more favourable prognosis associated with a more pronounced macrophage infiltration (Heidl et al, 1987;Tsujitani et al, 1987;Ohno et al, 2003). Similarly, increasing tumour-infiltrating lymphocyte count has been linked with decreased risk of death from gastric cancer in one study, but associated with an adverse prognosis in another (Setala et al, 1996;Grogg et al, 2003).…”
Section: Discussionmentioning
confidence: 81%
“…12,13 Induction of effective antitumor response requires DC to present tumor antigen, 14 but tumor cells often have limited expression of MHC antigens and costimulatory molecules, [15][16][17] and also tumor cells can produce immune inhibitory factors that inhibit DC maturation and migration. 18,19 It has been shown that the quantity of DC within tumors of a variety of histological types are correlated with prognosis, 20,21 and that DC which reside within the tumor are immature. 22 Thus efficient DC maturation, migration and activation might be of great importance for the induction of antitumor immunity.…”
Section: Activated DC To Produce High Levels Of Il-12 Furthermore Amentioning
confidence: 99%
“…18,19 In this study, we also demonstrated that migration of DC was inhibited by supernatants of 3LL (see Figure 3). It has been shown that the density of DC within tumors of a variety of histological types was correlated with prognosis, 20,21 and that DC within the tumor were immature. 22 So, both the infiltration of DC into the tumor and the migration and homing of DC from the tumor to lymphoid organs are considered to be critically initial steps during induction of antitumor immune response.…”
Section: Figure 6 Production Of Cytokines After MDC Gene Transfer In mentioning
confidence: 99%
“…the infiltration of tumours by DCs is thought to reflect the local immune response ). We reported previously that the survival time of patients with adsvanced gastric cancer w as correlated with the density of DCs that were positive for S-100 protein (Tsujitani et al 1987). Similar results hav-e been obtained by other groups who studied malignancies of the lung (Miyake et al 1992).…”
mentioning
confidence: 98%